Adopting Evaluative Conditioning to Improve Coach–Athlete Relationships - Li, Jie; Chen, Beibei; Zhang, Yu (Frontiers in Psychology, 2021)
Coach-athlete relationships are key to athletes' well-being, development, training, and sports performance. The present study explored the effect of an evaluative conditioning (EC) intervention on the improvement of coach-athlete relationships. We applied a six-week EC intervention to the athletes in a volleyball team with two of their coaches involved in the EC while the third coach taken as control. In the EC, we repeatedly presented the coaches' facial images (i.e., conditioned stimuli) together with positively valenced pictures and words (i.e., unconditioned stimuli) to the athletes. The results showed that the EC intervention led the athletes to recognize their coaches' neutral faces as showing more happiness, respond faster to coach-positive associations in the implicit association test (IAT), and give higher ratings to the coaches in the Coach-Athlete Relationship Questionnaire (CART-Q). The present study suggests that EC may be adopted as an effective intervention for coach-athlete relationships, altering athletes' affective associations with their coaches to be more positive and improving their explicitly evaluation of the relationship.